Regional integration policy, industrial chain and corporate total factor productivity: An econometric empirical analysis from China - Huang, Dawei; Chen, Gang; Han, Yonghui (Frontiers in Environmental Science, 2022)
This paper aims to investigate the impact, mechanism, and heterogeneity of regional integration policy (RIP) on firms' total factor productivity (TFP). We take the integration of Shenzhen-Dongguan-Huizhou policy (ISDHP) as the research object and conduct a multi-dimensional fixed-effect DID analysis based on China's listed A-share firms' data. The results show that RIP can significantly improve corporate TFP in the region, while it is more pronounced in the SOE group. The policy effects are robust after a series of robustness tests. In addition, we use a set of industry chain indicators to identify the mechanism between RIP and corporate TFP from the industry chain perspective. The results show that the ISDHP can improve corporate TFP by significantly improving the upstream degree of firms' industrial chain. Further research shows that the impact of ISDHP policies can also improve corporate TFP by innovating even the green innovating and improving market competitiveness. The state-owned listed firms have significant advantages in these mechanisms. In general, China's ISDHP has achieved the expected effect in improving enterprises' TFP. However, in the future, attention should be paid to the issues of “state tilt” and “private discrimination”.